2016
DOI: 10.3746/jkfn.2016.45.7.1001
|View full text |Cite
|
Sign up to set email alerts
|

Quality Characteristics of Modified Doenjang and Traditional Doenjang

Abstract: This study was conducted to investigate the relationship between quality factors and palatability of modified Doenjang and traditional Doenjang. Fourteen types of Doenjang, including three modified Doenjang and 11 traditional Doenjang samples, were analyzed to evaluate their physicochemical and sensorial properties. There were differences in e-tongue, which indicates overall acceptability. Water contents, minerals, total sugar contents, salt contents, pH, titratable acidity, and free amino acids of Doenjang di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…Intriguingly, organic acids were observed to be relatively higher in TD than ID. The organic acids in doenjang determine flavors such as acidity and sourness, which are major considerations when purchasing fermented foods [7,20]. We can speculate that the relatively abundant organic acids in TD might be achieved by anonymous fermentation microbes during long fermentation periods [7,16].…”
Section: Primary Metabolite Profiling Of Traditional and Industrial Doenjangmentioning
confidence: 99%
“…Intriguingly, organic acids were observed to be relatively higher in TD than ID. The organic acids in doenjang determine flavors such as acidity and sourness, which are major considerations when purchasing fermented foods [7,20]. We can speculate that the relatively abundant organic acids in TD might be achieved by anonymous fermentation microbes during long fermentation periods [7,16].…”
Section: Primary Metabolite Profiling Of Traditional and Industrial Doenjangmentioning
confidence: 99%
“…It changes metabolites of soybeans, and pH in TMD is normally about 5.3 and varies between 4.9–6.2. The pH discrepancy in TMD is related to the contents of Lactobacillus spp., yeast, and organic acids according to the fermentation periods [ 24 ]. In the present study, although pH was not measured in TMD, Lactobacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term aged soybean products (samples) showed a tendency to decrease in terms of number and types of strains when compared with short-term aged ones, while the amounts of amino nitrogen, free amino acid, lactic acid and some ester compounds, including functional compounds such as GABA , daidzein and genistein, increased [ 21 , 24 , 25 , 26 , 27 ]. Therefore, in consideration of the differences in compounds between short-term and long-term fermented soybean pastes, it is possible to find strains that produce a desirable flavor from long-term fermented soybeans.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, studies of long-term fermented Doenjang have reported an increase in the content of desirable flavor compounds such as ester like ethyl acetate and lactic acid as well as an increase in functional gamma-aminobutyric acid ( GABA ) [ 21 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%